Web Based Marketing Prospect Data Management Information System at Politeknik Ganesha Guru - Luh Putu Cintya Prabandari; Desak Nyoman Dewanggi Triananda Budidana (Jurnal Krisnadana, 2026)
Higher education in the modern era faces challenges along with the rapid development of technology. Educational institutions such as Politeknikik Ganesha Guru need to manage prospect data efficiently to remain relevant and competitive. Unstructured prospect data management is a major obstacle, with data scattered across multiple formats such as physical documents and spreadsheets, leading to duplication, inconsistency, as well as inaccurate data analysis. In addition, tracking the history of lead interactions, such as interest and required follow-ups, was difficult without a structured system, affecting personalization and follow-up effectiveness. Manual management also makes it difficult to access and update data in real-time, hampering the marketing team especially when off-campus. On the other hand, limitations in data analysis slow down the evaluation of marketing performance. The utilization of a web-based information system is expected to be an effective solution, as it can integrate data centrally, improve accessibility, and allow for more accurate analysis. With this solution, Politeknik Ganesha Guru can be more competitive in attracting potential students and improving educational services.